Tears of Sensibility - Sympathy a Poem - Let's all be Unhappy together i.e. The Wig Club in Distress - (:unkn) unknown (Fores, S. W., 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Whig Party (Great Britain); Fitzgerald, Edward, Lord, 1763-1798; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons